Challenges to the implementation of sustainable public procurement: an integrative review - Demarchi, Murilo Pedro; Guercio, Mary Jerusa; Sierra, Eduardo Juan Soriano (Seven Editora, 2023)
then a global scale, public procurement corresponds to about 12% of a nation's GDP. Sustainable Public Procurement (SPP) includes public purchases that adopt sustainability criteria in the bidding processes. The present study sought to investigate, through an integrative review, what would be the main existing challenges in the public sector that hinder the adoption of SPP practices. The results are aimed at challenges related to the degree of economic development of two countries and, also, for a given level of development. It was observed that the limited knowledge of two actors in purchases, in the absence of leadership and the absence of solid data and monitoring, are considered crucial factors for the improvement of this type of purchase, related to goal 12.7, of objective 12, of the UN 2030 Agenda.DOI: https://doi.org/10.56238/devopinterscie-005